MARKET VALUE ADDED (MVA), FINANCIAL RATIOS AND VALUE OF MANUFACTURING COMPANIES IN THE AUTOMOTIVE AND COMPONENT SUB-SECTORS - Agustin, Riska; Rochmawati, Reni (Universitas Nusa Cendana, 2025)
In the competitive automotive sector, understanding the factors that influence investor valuation is essential. This study examines how Market Value Added (MVA) and Return on Assets (ROA) affect firm value, measured by Tobin's Q ratio, in manufacturing companies within the automotive sector from 2021 to 2023. A quantitative methodology with an associative approach was applied, analyzing the financial statements of 11 companies listed on the Indonesia Stock Exchange. The findings reveal two key points: (1) MVA does not impact firm value, while (2) ROA significantly influences firm value in this sector. These results underscore the importance of efficient asset management for enhancing profitability and shareholder value. The study clarifies the relationship between MVA, ROA, and firm value, offering valuable insights for stakeholders. Ultimately, while MVA may not be a decisive factor, a strong ROA can significantly affect market perception and a company's financial success. Keywords: Market Value Added; Return On Assets; Tobin’s Q